Fred M. Donner's Views on Orientalist Thought about the Distinction between the Qur'an and Hadith - Fathurrohman, Rizal; Marhumah, Marhumah (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2022)
The purpose of this paper is to explore Fred M. Donner’s views on the distinction between the Qur'an and Hadith among orientalists. This study describes Donner's views on orientalist thought, especially John Wansbrough who stated that the Qur'an and Hadith originate from the same time. This paper uses a qualitative study in the type of library research with a descriptive qualitative analysis method to analyze and elaborate on the views of Fred M. Donner. The results of this study show that, in contrast to the hadiths which enthusiastically discuss political topics, the Al-Qur'an rarely provides answers about the political leadership of its followers. Second, unlike the hadiths, which are full of anachronistic allusions and explanations of earlier prophets, the Qur'an does not include any reference to events that occurred after previous prophets. Third, the textual vocabulary and preferences of the Qur'an and hadith when discussing religious practices vary. The contrast set forth above thus refutes claims made by non-Muslim academics that the hadith were created at the same time as the Qur'an or were written before it. Because the hadith was made after the date of birth of the Qur'an, in a certain setting.